2010
DOI: 10.4315/0362-028x-73.5.960
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Properties of for Probiotic or Protective Culture Use

Abstract: Pediococcus parvulus 2.6 (previously Pediococcus damnosus 2.6, here confirmed as P. parvulus by 16S DNA sequencing) displayed antibacterial activity toward several bacterial species, including isolates found as contaminants in oats, herein genetically identified as Bacillus cereus. No inhibition of Listeria monocytogenes was found under the conditions used. Antibacterial activity was retrieved after ammonium sulfate or acetone precipitation showed it to be peptide mediated. P. parvulus 2.6 has previously shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In the present study both Pd 2.6 R and NR was isolated from faeces showing the ability of this LAB to survive the passage through the mouse gastrointestinal tract. The survival in the gut is a prerequisite for probiotic bacteria (FAO/WHO 2002) and the survivability of Pd 2.6 previously investigated in vitro (Fernández de Palencia et al 2009; Immerstrand et al 2010) was confirmed. The previous in vitro trial showed that the presence of EPS does not confer an advantage of survival for Pd 2.6 in the digestive tract (Fernández de Palencia et al 2009) however when the EPS is heterologously expressed in Lactobacillus paracasei it gives an advantage of survival to both technological and gastrointestinal stresses compared to the wild type strain (Stack et al 2010).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present study both Pd 2.6 R and NR was isolated from faeces showing the ability of this LAB to survive the passage through the mouse gastrointestinal tract. The survival in the gut is a prerequisite for probiotic bacteria (FAO/WHO 2002) and the survivability of Pd 2.6 previously investigated in vitro (Fernández de Palencia et al 2009; Immerstrand et al 2010) was confirmed. The previous in vitro trial showed that the presence of EPS does not confer an advantage of survival for Pd 2.6 in the digestive tract (Fernández de Palencia et al 2009) however when the EPS is heterologously expressed in Lactobacillus paracasei it gives an advantage of survival to both technological and gastrointestinal stresses compared to the wild type strain (Stack et al 2010).…”
Section: Discussionmentioning
confidence: 84%
“…The LAB Pediococcus parvulus derived from alcoholic beverages has a great capacity to withstand environmental stress (Dols-Lafargue et al 2008) and it has been shown to resist gastrointestinal stress in vitro (Fernández de Palencia et al 2009; Immerstrand et al 2010). P. parvulus 2.6 (Pd 2.6) has been isolated as a contaminant in Basque Country cider (Fernandez et al 1995) and it produces a 2-substituted (1,3)-β-D-glucan (β-glucan) that is excreted into the surroundings as a ropy EPS causing unwanted alterations to the beverage known as ropiness; long slimy filaments of EPS may be picked up from the liquid (Duenas-Chasco et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The EPS synthesising strains have been proposed as suitable for production of ropy dairy products (Elizaquível et al., ) but they have not been included in any commercial products. Similarly, it appears that EPS‐producing strains are less susceptible to simulated and mice digestive conditions, while lowering the cholesterol levels (Immerstrand et al., ; Lindström et al., ) reason why they have been proposed as potential probiotics but never used as such or intentionally added to any food. P. parvulus is, however, frequently found in fermented foods (Mesas et al., ; Abriouel et al., ; Bağder Elmacı et al., ) and feed, such as silage (Tohno et al., ), and thus there is frequent exposure to it without any signs of pathogenicity for humans or animals.…”
Section: Assessmentmentioning
confidence: 99%
“…The former confers an oily appearance to the liquid known as ropiness, while the latter generates a butter-like flavour. Similarly, it appears that EPS-producing strains are less susceptible to simulated and mice digestive conditions, while lowering the cholesterol levels (Immerstrand et al, 2010;Lindstr € om et al, 2013) reason why they have been proposed as potential probiotics but they were never used as such nor intentionally added to any food. The EPS synthesising strains have been proposed as suitable for production of ropy dairy products (Elizaqu ıvel et al, 2011) but they have not been included in any commercial products.…”
Section: Body Of Knowledgementioning
confidence: 99%